Revealing the rise of a living fossil menagerie - Lidgard, Scott; Kitchen, Emma (Frontiers in Ecology and Evolution, 2023)
The living fossil concept continues to foster development of integrative research, as it has done since Darwin’s use of the term in 1859. It has been applied to a vast menagerie of biological entities across the kingdoms of life and at many levels in the biological hierarchy. Correspondingly, a number of primary living fossil criteria emerged and persisted all the while as disciplines, theories and practices of biology transformed. In this paper we attempt the first comprehensive analysis of the use of the term 'living fossil' from 1860 to the present. Employing a compilation of 719 publications and 853 unique entities, we examine: (1) patterns of change in the phylogenetic diversity of living fossils, their taxonomic ranks and groups, (2) the diverse subject areas in which living fossils play a role, and (3) the primary criteria used to designate living fossil status. Our analyses reveal how the menagerie has extended and diversified alongside technological developments in biological research. The average number of living fossil criteria applied per entity has escalated even more rapidly than the menagerie has expanded. We argue that the demonstrated persistence, ever-expanding scientific and public interest, and future utilization of living fossils reflects increasingly complex challenges to deep-seated expectations at the heart of a living fossil research agenda: omnipresent evolutionary change and inevitable disappearance or extinction.